A review on pre-development project stage in Malaysia landscape architecture industry - Mohd Hanaizal, Fatin Ariena; Mansor, Mazlina (2019)
Landscape architecture profession plays an important role in the built environment projects that conserve environment especially in a cityscape. Landscape architecture profession in Malaysia was officially formed in 1981 under the name Angkatan Lanskap Arkitek Malaysia (ALAM) and now with the name Institute Landscape Architecture Malaysia (ILAM), the organisation acts as an official body to manage the landscape architecture industry. The paper aims to review the process of project development in landscape architecture industry. Thus, it also identifies challenges that are faced by professionals in the field in managing the process in the local landscape architecture industry. Landscape project development can also be termed as project life cycle (PLC) in the construction industry. It is a process of planning and controlling the overall tasks or activities within the project, therefore harness resources available for the activities, e.g. people, materials, time, money, knowledge, equipment and spaces. The process consists of three important stages: (a) pre-development stage, (b) construction stage, and (c) post-construction stage. Review has suggested that the process can also be divided into more than three stages. The most significant challenge is that majority of professionals in the field are not well-verse with all the stages of work that happen in the project development. This is due to fragmented experience only in certain stages of the work, and there are no definite source of reference that they can refer to. Thus, this study is significant to documents the overall tasks in the PLC as a set of reference for the professionals. All in all, it is hoped that the research will be able to contribute to the inauguration of landscape architecture position in Malaysia by providing a set of reference that can be further implemented for practical improvement in local landscape industry.